Internalization of National Values as a Strategy to Strengthening Religious Moderation in Ma'had Aly (Case Study of Ma'had Aly Attaqwa KH. Noer Alie, Bekasi) - Huda, Ade Naelul; Fitriana, Muhammad Azizan (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
This study aims to reveal the forms of internalization of the value of national commitment as a strategy to strengthen religious moderation by the manager of Ma'had Aly Attaqwa KH. Noer Alie, Bekasi. Ma'had Aly is a pesantren higher education established to produce pesantren cadres. In addition to studying, Ma'had Aly students also have the task of serving, namely representing kyai guiding the daily activities of students at the Islamic Boarding School. Their high intensity with students has implications for the views and religious values of the students in the Islamic boarding school. This research uses qualitative methods in the form of  field research  or field research. The collected data is then analyzed using descriptive analysis. The results showed that religious moderation in Ma'had Aly Attaqwa KH. Noer Alie stands out for strengthening aspects of national commitment. The results of the study also prove that strengthening religious moderation is applied through the integration of learning activities, social and extracurricular activities as well as library literacy. Mahasantri Ma'had Aly Attaqwa KH. Noer Alie is equipped with the values of struggle and nationalism adopted from the struggle values of its founder KH. Noer Alie, a cleric and freedom fighter who was awarded the title of national hero. The results of the study contribute as a policy reference for the strategy of developing religious moderation in the Ma'had Aly environment for the Directorate General of Diniyah Education and Islamic Boarding Schools of the Ministry of Religious Affairs of the Republic of Indonesia.